Investigation of Preservice Teachers' Achievement in Dissolution Through CHAID analysis - Şen, Şenol; Yılmaz, Ayhan (Bartın Üniversitesi, 2017)
The aim of this study was to investigate the relations between preservice teachers' achievement in dissolution, learning approaches, motivation and scientific epistemological beliefs through CHAID analysis. The study was conducted with correlational research design, which is one of the quantitative research methods. For this purpose, a total of 618 preservice teachers participated in the study. The dissolution concept test, the revised two?factor study process questionnaire (R?SPQ?2F), chemistry motivation questionnaire and scientific epistemological beliefs survey were used as data collection tools. CHAID (Chi-squared Automatic Interaction Detection) analysis was used to analyze the data of the study. At the end of the study, a significant effect of preservice teachers' scientific epistemological beliefs, career motivation and surface learning approaches on their achievement was determined. In addition, results of CHAID analysis showed that the scientific epistemological beliefs were the most important predictor of preservice teachers' achievement in dissolution.

Bu çalışmanın amacı öğretmen adaylarının çözünme konusundaki başarıları ile öğrenme yaklaşımları, motivasyonları ve bilimsel epistemolojik inançları arasındaki ilişkileri CHAID analizi ile incelemektir. Çalışma nicel araştırma yöntemlerinden biri olan ilişkisel araştırma yöntemiyle yürütülmüştür. Bu amaçla çalışmaya 618 öğretmen adayı katılmıştır. Çalışmada veri toplama aracı olarak çözünme kavram testi, öğrenme yaklaşımları envanteri, kimya motivasyon ölçeği ve bilimsel epistemolojik inanç ölçeği kullanılmıştır. Çalışmada elde edilen verilerin analizinde CHAID (Chi-squared Automatic Interaction Detection) analizi kullanılmıştır. Çalışmanın sonunda, öğretmen adaylarının bilimsel epistemolojik inançlarının, kariyer motivasyonlarının ve yüzeysel öğrenme yaklaşımlarının başarıları üzerinde anlamlı bir etkisi olduğu belirlenmiştir. Ayrıca CHAID analizi, öğretmen adaylarının çözünme konusundaki başarılarını yordayan en önemli değişkenin bilimsel epistemolojik inançlar olduğunu ortaya koymuştur.
Öğretmen Adaylarının Çözünme Konusundaki Başarılarının CHAID Analizi ile İncelenmesi